Intrinsic properties and neuropharmacology of midline paraventricular thalamic nucleus neurons. - Kolaj, Miloslav; Zhang, Li; Hermes, Michael L.; Renaud, Leo P. (Frontiers in Behavioral Neuroscience, 2014)
Neurons in the midline and intralaminar thalamic nuclei are components of an interconnected brainstem, limbic and prefrontal cortex neural network that is engaged during arousal, vigilance, motivated and addictive behaviors, and stress. To better understand the cellular mechanisms underlying these functions, here we review some of the recently characterized electrophysiological and neuropharmacological properties of neurons in the paraventricular thalamic nucleus (PVT), derived from whole cell patch clamp recordings in acute rat brain slice preparations. PVT neurons display firing patterns and ionic conductances (IT and IH) that exhibit significant diurnal change. Their resting membrane potential is maintained by various ionic conductances that include inward rectifier (Kir), hyperpolarization-activated nonselective cation (HCN) and TWIK-related acid sensitive (TASK) K+ channels. Firing patterns are regulated by high voltage-activated (HVA) and low voltage-activated (LVA) Ca2+ conductances. Moreover, transient receptor potential (TRP)-like nonselective cation channels together with Ca2+- and Na+-activated K+ conductances (KCa; KNa) contribute to unique slow afterhyperpolarizing potentials (sAHPs) that are generally not detectable in lateral thalamic or reticular thalamic nucleus neurons. We also report on receptor-mediated actions of GABA, glutamate, monoamines and several neuropeptides: arginine vasopressin, gastrin-releasing peptide, thyrotropin releasing hormone and the orexins (hypocretins). This review represents an initial survey of intrinsic and transmitter-sensitive ionic conductances that are deemed to be unique to this population of midline thalamic neurons, information that is fundamental to an appreciation of the role these thalamic neurons may play in normal central nervous system (CNS) physiology and in CNS disorders that involve the dorsomedial thalamus.